Reflections of Evangelical Missions and Missionary Activities in Nineteenth-Century Lithuanian Periodicals of Prussian Lithuania - Pocytė, Silva; Rekašiūtė, Kotryna (Senoji Lietuvos literatūra, 2024)
The organisation of church missions, which began in Europe in the eighteenth century, was especially active in England and Prussia in the nineteenth century. The Lithuanians of Prussian Lithuania, which belonged to the Kingdom of Prussia until 1871 and to the German Empire from 1871, were also involved in evangelical missions in the nineteenth century. Collecting donations for missions and sending young lietuvninkai (Prussian Lithuanians) to missionary schools was an inseparable aspect of the religious life of the Lithuanians in Prussian Lithuania in the nineteenth century, which was closely related to the general process of spreading of European civilisational phenomena and the dissemination of Christianity in the non-Christian lands of Asia and Africa. The article analyses the reasons for the formation of evangelical missions in the nineteenth-century European context and in the Prussian state and introduces the missionary societies that educated missionaries and sent them to Asia and Africa. The text introduces the first missionary societies established in Prussia in Königsberg (founded in 1822) and Berlin (1824) and the most important leaders of the nineteenth-century missionary organisation in Berlin, Hermann Theodor Wangemann and Johannes Evangelist Gossner. The article discusses the reasons behind the involvement of Prussian Lithuanians in missionary activities: collecting donations for the implementation of missions and sending young people to serve in missions, mostly in Asia (India and China). The study sheds light on the activities of evangelical missions by analysing nineteenth century Lithuanian periodicals of Prussian Lithuania related to the activities of evangelical missions and missionaries. Emphasis is placed on analysing the content of the newspaper Nusidavimai apie Evangelijos prasiplatinimą tarp žydų ir pagonių (Stories about the Spread of the Holy Write among Jews and Heathens) edited by Johann Ferdinand Kelkis, the first publisher of Lithuanian periodicals. In the nineteenth and the early twentieth century, mission-related information was also published in other Lithuanian-language periodicals: Keleivis (The Wayfarer), Lietuviška ceitunga (The Lithuanian Newspaper), Tilžės keleivis (The Wayfarer of Tilžė), and others. These publications were popular among the Lithuanian-reading community: they consolidated their piety and allowed them to participate in important processes unfolding in the Christian world.The popularity of the periodicals devoted to missions among Prussian Lithuanians can be explained by the fact that they were familiar with missionary work not only from the pages of newspapers but also from direct participation in their activities. A dozen or so young Prussian Lithuanians became missionaries, preaching that, albeit only a small Protestant handful, Prussian Lithuanians could be involved in the work of strengthening and spreading Christianity to the whole evangelical world. From the 1860s, more than forty Prussian Lithuanians worked in evangelical missions in Africa and Asia (mainly in India and China). It was useful for Lithuanian young people to take part in missions: for poor Lithuanians, German missionary schools often were the only opportunity not only to receive a higher education or to learn foreign languages but also to travel and to know foreign lands. Many of the Prussian Lithuanian missionaries were also active figures in writing who used to send texts and letters about their ministry in distant lands to the Lithuanian press.The article analyses a number of texts of this kind, the content of which not only helped to reveal the aspects of the involvement of Prussian Lithuanians in missionary activities and the daily routine of missionaries, but also illustrated the change in the mental world of the Lithuanian-reading community, where, next to the texts of a purely religious nature, information and facts about the peoples of the various continents, their ethnography, history, and geography were provided.
Keywords: Prussian Lithuania; Protestant Church; evangelical missions; missionaries; Lithuanian periodicals